The pharmacokinetics of orally administered butylscopolamine in greyhound dogs. Issue 6 (3rd August 2018) - Morris, Tim; Paine, Stuart W.; Viljanto, Marjaana; Hudson, Simon; Gower, Simon; Pittorino, Melissa; Colgan, Sally
Abstract: The oral tablet formulation of butylscopolamine, which is available without prescription, is commonly used by trainers of racing greyhounds to treat functional urethral obstruction. As medication control of butylscopolamine is therefore required for such use to ensure the integrity of greyhound racing, an administration study was performed in six greyhounds to determine the pharmacokinetics of orally administered butylscopolamine. A single dose of one 10 mg butylscopolamine tablet was administered orally to simulate this use in greyhound racing. Blood, urine and faeces were collected at regular intervals from the greyhounds for up to 9 days and butylscopolamine concentrations determined. There was some, but very limited, absorption of butylscopolamine, with rapid elimination from plasma with a mean half‐life of 2 hr. Urine concentrations initially declined in a similar manner to the plasma pharmacokinetics but then entered a much longer half‐life of approximately 50 hr. Faecal concentrations declined to very low levels between 48 and 120 hr. The use of orally administered butylscopolamine for functional urethral obstruction in greyhounds is unjustified due to this very limited drug absorption. Medication control of butylscopolamine's antispasmodic effect on the digestive tract is possible by setting screening limits based on the urinary and faecal drug levels as determined in this study.